Detailed breast cancer pathology data for large-scale studies – access and completeness in NSW, Australia - Mark J Bartlett; Valerie Beral; Xenia Dolja-Gore; Toral Gathani; Bette Liu (Public Health Research & Practice, 2021)
Objectives: We sought to determine the ease with which breast cancer pathology data could be ascertained for a large cohort of Australian women, to support epidemiological research.